Surface engineering of cellulose film with myristic acid for high strength, self-cleaning and biodegradable packaging materials. (1st October 2021) - Chen, Qianqian; Chang, Chunyu; Zhang, Lina
Abstract: Developing sustainable, renewable, hydrophobic, and biodegradable packaging material to replace petroleum-based plastic products remains a challenge. Herein, original cellulose/myristic acid composite films were fabricated by solvent-vaporized controllable crystallization of natural myristic acid on anisotropic cellulose films. The myristic acid crystals that evenly distributed on the surface of cellulose film generated micronano binary structure and the interstitial space between microplates, resulting in high hydrophobicity (water contact angle = 132°) and excellent self-cleaning property of the composite film. The resultant film exhibited good tensile strength and toughness under both dry (188.7 MPa, 34.4 MJ m −3 ) and humid conditions (119.9 MPa, 28.7 MJ m −3 ). Moreover, these composite films could be degraded completely after approximately 102 days in soil with an average environment temperature of 32 °C. This work provided a low-cost and sustainable pathway for the fabrication of high-strength, self-cleaning, and waterproof packaging materials instead of plastics. Highlights: Hydrophobic materials were fabricated by surface modifying cellulose film with myristic acid. Solvent-vaporized crystallization enabled the films hydrophobicity and self-cleaning. The resultant films exhibited good mechanical performances under both dry and humid conditions. The resultant films could be completely degraded in soil after approximately 102 days.